Global positioning system-derived workload metrics and injury risk in team-based field sports: A systematic review - Kupperman, N.; Hertel, J. (Journal of Athletic Training, 2020)
Objective: To evaluate the current literature regarding the utility of global positioning system (GPS)-derived workload metrics in determining musculoskeletal injury risk in team-based field-sport athletes. Data Sources: PubMed entries from January 2009 through May 2019 were searched using terms related to GPS, player workload, injury risk, and team-based field sports. Study Selection: Only studies that used GPS metrics and had injury as the main outcome variable were included. Data Extraction: Total distance, high-speed running, and acute : chronic workload ratios were the most common GPS metrics analyzed, with the most frequent sports being soccer, rugby, and Australian rules football. Data Synthesis: Many distinct workload metrics were associated with increased injury risk in individual studies performed in particular sport circumstances; however, the body of evidence was inconclusive as to whether any specific metrics could consistently predict injury risk across multiple team-based field sports. Conclusions: Our results were inconclusive in determining if any GPS-derived workload metrics were associated with an increased injury risk. This conclusion is due to a myriad of factors, including differences in injury definitions, workload metrics, and statistical analyses across individual studies.